The Use Of Computer Assisted Language Learning (Call) To Improve The Students’ Speaking Skill Of Grade X C Sma N 4kota Bima In Academic Year 2022/2023 - Rizkiani, Firliah; Budiman, Arif; Firmansyah, Firmansyah; Adilansyah, Adilansyah; Hendra, Hendra (JUPE : Jurnal Pendidikan Mandala, 2023)
Globalization becomes a current issue all over the world. It expands and accelerates the exchange of ideas and commodities over vast distances. Regional economies, societies, and cultures have become integrated through a global network of communications, transportation, and computer technology. These have given impetus and make the world more interdependent than ever (http://en.wikipedia.org/wiki/Globalization). Globalization is no longer about trade in things that can be put in a box, but about trade in everything that can be digitalized. Digital technology makes everything simple. A big problem appears in a trade is distance, but it can be solved by using computer and internet connection. Sale and purchase transaction can be done by using computer with the Internet connection. Computer gives important contribution in globalization. Hornby (1995: 235) states that computer is an electronic device for strong and analyzing information fed into it, for calculating, or for controlling machinery automatically. Computer is used in vary of field and computer also used in instruction. Computer used in instruction provides virtually instantaneous response to the students input, has extensive capacity to store and manipulate information, and is unmatched in its ability to serve many individual students simultaneously. It has the ability to control and integrate a wide variety of media – still pictures, graphics, and moving images, as well as printed information. The computer can also record, analyze, and react to students’ responses that are typed on a keyboard or selected with a mouse (Heinich, 1996: 228).